FACTORS AFFECTING CAREER PLANNING: SKILL AND EXPERIENCE (LITERATURE REVIEW OF HUMAN RESOURCES MANAGEMENT) - Rajab, Muhammad (Dinasti International Journal of Digital Business Management, 2021)
Literature review article on the influence of ability and experience on career planning is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Ability influences Career Planning; 2) Experience has an effect on Career Planning. Apart from these 2 exogenous variables that affect the endogenous variable Career Planning, there are still many other factors including the variables of Leadership, Corporate Finance, Motivation, Employee Performance.